2017
DOI: 10.3126/jaar.v3i2.16757
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Prevalence of Drug Abuse in youth: Cases from the Surkhet District of Nepal

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In the present study, we found that some similarities the age at first drug using by the respondent was 17.1 years and above 50% were employed, which is similar to the nationally published survey report by ministry of home affairs drug control programreported (15-19) years was the age for first drug intake and more than 50% drug user were employed [12]. However, this findings of our study contradictory to some recently publish paper [13,14]. Our study has some important strengths first of all we enrolled from different socio economic representatives of different districts.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…In the present study, we found that some similarities the age at first drug using by the respondent was 17.1 years and above 50% were employed, which is similar to the nationally published survey report by ministry of home affairs drug control programreported (15-19) years was the age for first drug intake and more than 50% drug user were employed [12]. However, this findings of our study contradictory to some recently publish paper [13,14]. Our study has some important strengths first of all we enrolled from different socio economic representatives of different districts.…”
Section: Resultssupporting
confidence: 70%
“…Socio-Demographic Information of the RespondentTable IIrepresents the (59%) entered into drug habit during 15-19 years of age. among these categories, 23% male and 22% female initiated drug use even at a teenier age(10)(11)(12)(13)(14)…”
mentioning
confidence: 99%